Is health condition affect the online health information seeking behavior? a report from Indonesia - Atina Husnayain; Lastdes Cristiany Friday; Anis Fuad (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Background: Google Trends has increasingly received attention as the potential data source for diseases surveillance in the last two decades. In Indonesia, Google Trends was detected as a novel predictor for dengue outbreak in national and sub-national level. Although the accuracy depended on online information seeking behavior, no study was performed at the state level. This approach is necessary to be assessed in order to measure the representativeness of the online health information seeking pattern captured by Google Trends. Objective: This study aimed to examine the online health information seeking behavior according to the history of health condition among Indonesian aged 15-60 years old. Methods: Online health information seeking behavior’ survey was conducted in 2017, involved 385 respondents. Questions were asked in three different parts including the online health information seeking in general, the use of social media, and the use of search engines. Statistical analysis was conducted using Prevalence odds ratio (POR) in Stata version 13. Results: Prevalence odds ratio analysis shows that person who ever experiences ill in the last three months is 1.63 (CI 95% 1.06-2.50) more likely to have access to the online health information on the Internet. Online health information seeking behavior seem to be in-line both using social media and search engines. The person who ever experiences ill in last three months is more likely to have access to the online health information on social media (POR 1.60; CI 95% 0.95-2.74) and search engines (POR 2.89; CI 95% 1.63-5.28). Moreover, looking for disease information on social media (POR 1.61; CI 95% 1.04-2.49) and search engines (POR 2.23; CI 95% 1.43-3.51) also influenced by health condition. Conclusions: History of health condition affects online health information seeking behavior. Further research needs to assess the Indonesian online health information seeking behavior related to a certain disease.